Seeing Colors: Cultural and Environmental Influences on Episodic Memory. (December 2017) - Persaud, Kimele; Hemmer, Pernille; Kidd, Celeste; Piantadosi, Steven
Expectations learned from our perceptual experiences, culture, and language can shape how we perceive, interact with, and remember features of the past. Here, we questioned whether environment also plays a role. We tested recognition memory for color in Bolivia's indigenous Tsimanè people, who experience a different color environment than standard U.S. populations. We found that memory regressed differently between the groups, lending credence to the idea that environmental variations engender differences in expectations, and in turn perceptual memory for color.